A research on the determination of individual competencies by statical methods - Bozkurt, Tülay (My University, 2009)
reysel Yetkinlikler, Ekonomik Kriz ÖZET BİREYSEL YETKİNLİKLERİN İSTATİSTİKSEL YÖNTEMLERLE BELİRLENMESİ ÜZERİNE BİR ARAŞTIRMA Bireysel yetkinlikler, bilgi, beceri, motivasyon, düşünce ve duygu yapısı gibi bir çok faktörden oluşan ve bir işi başarıyla sonuçlandırmak için sergilenen davranışların tümüdür. Çalışan bir kişinin yetkinlik özellikleri, kişisel yapısına, işin içeriğine, çalıştığı kurumun ve içinde bulunduğu ortamın koşullarına göre değişim göstermektedir. Bir işi başarıyla yerine getiren bir kişinin farklı bir işte ve çalışma ortamında farklı yetkinliklere ihtiyaç duyduğu görülmektedir. Özellikle normal çalışma koşulları içerisinde bireyin sergilediği davranışlar başarılı sonuçlar almasını sağlarken hızlı değişimlerin yaşandığı ve ekonomik kriz gibi karmaşanın hakim olduğu durumlarda aynı yetkinlikler yeterli olmamaktadır. Bu araştırma, çalışanların normal koşullarda sergilemiş olduğu yetkinliklerle kriz durumunda sergilemiş olduğu yetkinlikleri karşılaştırarak yeni bir “Yetknlik Modeli” sunmaktadır. Individual Competencies, Economic Crisis

A RESEARCH ON THE DETERMINATION OF INDIVIDUAL COMPETENCIES BY STATISTICAL METHODS Individual Competencies consisting of various factors like knowledge, skills, motivation, thinking styles and emotions is a set of behaviors to be able to perform a work successfully. Being a competent person can show differentiation based on the personal characteristics, work structure, company and environmental conditions. While a person who can perform specifically a job with a required output same success can not be gathered for another job at another workplace. Besides under the normal working conditions individual competencies can cause superior performance however same sort of behaviors can be trivial at fast changing environmental conditions as chaos situation in economic crisis. This research finds out and compares the differences of the individual competencies performing under the normal and crisis conditions and presents the results in a new set of “Competency Model”.
Keywords: Bireysel Yetkinlikler; Ekonomik Kriz; Ekonomik Kriz_İstatistik; Sayısal Yöntemler